2018
DOI: 10.1371/journal.pone.0200690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of work-interval duration and sport specificity on blood lactate concentration, heart rate and perceptual responses during high intensity interval training

Abstract: The aim of this study was to examine the impacts on blood lactate concentration, measured heart rate and assessment of perceived exertion during split sessions of equal relative load, as also their relationship to the specific sport practised. Nineteen regional-level athletes (nine middle and long-distance runners (cyclic group) and ten field-sport team players (acyclic group)) performed four high-intensity interval training (HIIT) sessions with work-interval durations of 10 s, 50 s, 90 s and 130 s. The sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Furthermore, the present study’s results challenge the interpretation that increased duration of interval sets leads to lower perceived exercise enjoyment. Although we did not measure blood lactate concentration in the present study, a previous study reporting lower blood lactate concentration following interval sets greater than 4 min in duration (Valstad et al, 2018) compared with a substantially higher blood lactate concentration during supramaximal sprints (Wiewelhove et al, 2016; Warr-di Piero et al, 2018) may indicate a lower anaerobic contribution in interval set durations over 4 min compared with shorter interval set durations. Moreover, it has previously been suggested that negative affective responses are observed at supramaximal intensities (Ekkekakis et al, 2011).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Furthermore, the present study’s results challenge the interpretation that increased duration of interval sets leads to lower perceived exercise enjoyment. Although we did not measure blood lactate concentration in the present study, a previous study reporting lower blood lactate concentration following interval sets greater than 4 min in duration (Valstad et al, 2018) compared with a substantially higher blood lactate concentration during supramaximal sprints (Wiewelhove et al, 2016; Warr-di Piero et al, 2018) may indicate a lower anaerobic contribution in interval set durations over 4 min compared with shorter interval set durations. Moreover, it has previously been suggested that negative affective responses are observed at supramaximal intensities (Ekkekakis et al, 2011).…”
Section: Discussionmentioning
confidence: 68%
“…However, multiple high intensity interval exercise session designs are found in the studies investigating exercise enjoyment (Oliveira et al, 2018), which limits their comparability. These differences include variations in interval duration, ranging from seconds (Price and Moss, 2007; Wiewelhove et al, 2016; Warr-di Piero et al, 2018), to 1 min (Jung et al, 2014; Heisz et al, 2016) and bouts of up to 3 min (Bartlett et al, 2011; Decker and Ekkekakis, 2017); a previous study reported that longer interval sets are less enjoyable compared with those of shorter durations (Martinez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since blood LA following SIE greatly increased in the present study, we cannot rule out that the improvement in cognitive functions resulted from the acceleration of cerebral LA metabolism along with neuroprotective proteins induction. However, various highintensity interval training protocols could differently affect blood LA synthesis (Wood et al, 2016;Warr-di Piero et al, 2018). SIE is characterized by high LA production whereas longer protocols could rely more on aerobic metabolism, with lower LA synthesis (Astorino and Sheard, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study’s high-intensity intervals may have been too short to strain the anaerobic metabolic system and induce sufficient release of lactate. Previous studies have demonstrated that exercise protocols with shorter high-intensity interval durations result in lower blood lactate concentrations after exercise 33 . Lactate may be an important metabolic component for several reasons.…”
Section: Discussionmentioning
confidence: 99%